Correlation between In Vitro Susceptibility of Scedosporium apiospermum to Voriconazole and In Vivo Outcome of Scedosporiosis in Guinea Pigs - Capilla, Javier (American Society for Microbiology, 2004)
We have evaluated the efficacy of voriconazole (VRC) in a systemic infection by Scedosporium apiospermum in immunodepressed guinea pigs. Animals were infected with two strains; one required a VRC MIC of 0.5 to 1 μg/ml, common for this fungus, and the other required a high MIC (8 μg/ml), unusual in this species. VRC prolonged survival and reduced fungal load in kidney and brain tissues of the animals infected with the first strain but was unable to prolong survival or to reduce fungal load in brain tissue for the latter strain.